Psikoedukasi Prophetic Parenting pada Orangtua Siswa TK ABA Nganggring Turi Sleman Yogyakarta - Nurul Hidayah; Yuzarion Yuzarion; Dini Yuniarti; Fuadah Fakhruddina; Selasih Selasih; Casminto Casminto (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This prophetic parenting psychoeducation is one of a series of large programs in the form of strengthening psychospiritual and economic resilience for parents of ABA Nganggring Kindergarten students, Turi District, Sleman Regency, Special Region of Yogyakarta. The program aims to increase understanding and awareness of the importance of implementing prophetic parenting. The empowerment method chosen was psychoeducation with the target parents of students, which was carried out for three meetings, starting from the assessment, core program, and follow-up plans. The program participants were 30 parents/guardians of ABA Nganggring Kindergarten students. The result of implementing the program is that they have an adequate understanding of prophetic parenting for program participants. Through prophetic parenting psychoeducation, parents' awareness about the importance of applying prophetic parenting to children at home began to grow and support groups were formed to solve parenting problems in daily life. It is recommended that this psychological strengthening program be followed by a continuous care assistance program for the support groups that have been formed.